SYNTHESIS OF ANESTHESIN FROM P-AMINOBENZOIC ACID (Modern education and development, 2024)
Among the many thousands of derivatives of p-aminobenzoic acid, a number of effective local anesthetics have been found - substances that suppress the sensitivity (excitability) of nerve endings